Begonia ostulensis (Begoniaceae), a new species from Michoacán, Mexico - Martínez-Gordillo, Martha; Ramos-Ordoñez, María Felix (Phytotaxa, 2022)
Begonia ostulensis sp. nov. is a new species from section Knesebeckia, known solely from the state of Michoacán; it is similar to Begonia monophylla, an endemic species from Mexico with a distribution in the states of Mexico, Colima, Michoacán, Guerrero and Morelos, but B. ostulensis differs from it in having an orbicular, peltate, solitary leaf, with the lower and upper surfaces glabrous, a lobed and double-dentate, non-ciliate margin, inflorescences terminal, peduncle and rachis glabrous and fruit with primary wing asymmetrically triangular, glabrous.